Changes of Rheological Properties During Various Degrees of Knee Flexion after Meniscectomy - Aneta Vránová; Monika Šorfová; Petr Kubový (Karolinum Press, 2015)
Aim of this article is to find out if there is any difference in rheological properties in various degrees of flexion in the knee with meniscal tear and compare the results with measurement after physical activity. Experimental measurements were done by using the method of biorheometry which detects the passive resistance of the knee in movement from flexion to extension. We found changes of rheological properties in higher degrees of knee flexion with typical rising followed by fall of biorheogram around flexion of 80°. They were more remarkable after physical activity. Changes of rheological properties were more expressive in patients who have undergone meniscectomy a few years ago than changes in patients with recent meniscectomy.